2001
DOI: 10.1017/s0022029901004848
|View full text |Cite
|
Sign up to set email alerts
|

Lactation failure in crossbred Sahiwal Friesian cattle

Abstract: Milk producers in Malaysia make extensive use of crossbred Sahiwal Friesian dairy cattle. These animals have, however, been found susceptible to lactation failure. A survey of cows in an experimental herd of F1 Sahiwal Friesian animals indicated that, in 30% of animals, milk yield decreased to negligible levels within the first 8 weeks post partum. Lactation failure was associated with a progressive increase in the amount of residual milk left in the udder after normal milking. By week 3 of lactation, residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
1
8
0
2
Order By: Relevance
“…Additionally, all experimental groups produced milk at levels comparable with those described by other authors [7,20], and the Gir and GirHol groups did not exhibit a high percentage of residual milk as described for other zebu breeds [15] or for dairy cows submitted to different situations of stress [7,32] or during first milkings after parturition [6,16]. This confirms that CORT levels alone are often poor predictors of stress in lactating animals as reported by other research [33] and suggests that, if stress exists in Gir cows, it is not very acute and only concerns some animals in the group.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, all experimental groups produced milk at levels comparable with those described by other authors [7,20], and the Gir and GirHol groups did not exhibit a high percentage of residual milk as described for other zebu breeds [15] or for dairy cows submitted to different situations of stress [7,32] or during first milkings after parturition [6,16]. This confirms that CORT levels alone are often poor predictors of stress in lactating animals as reported by other research [33] and suggests that, if stress exists in Gir cows, it is not very acute and only concerns some animals in the group.…”
Section: Discussionsupporting
confidence: 84%
“…In other countries, some Bos indicus breeds are also susceptible to lactation failure [14,15] and retain high volumes of residual milk [15]. Disturbance of milk ejection can be attributed to a selective inhibition of OT release from the hypophysis gland as described after weaning [8,16]; in this case, normal milk ejection can be established after OT administration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other authors have observed that crossbred cows susceptible to lactation failure exhibit high residual milk, and have suggested that inhibition of OT release is a possible explanation for lactation failure [26]. This could explain why cows with poor milk yield depend on frequent udder stimulation, and in many cases present a failure of lactation when submitted to the classical management strategy of 2 exclusive milkings/day.…”
Section: Discussionmentioning
confidence: 77%
“…In crossbred GyrrHolstein cows, Negrao & Marnet (2002) demonstrated similar OT release and similar milk yields in exclusively machine milked cows compared with a combined suckling and milking regime, whereas Murugaiyah et al (2001) reported reduced milk yields and increased apoptotic activity in exclusively machine milked crossbred SahiwalrHolstein cows. However, increased OT release and milk yields due to suckling even in highyielding Holstein cows that are adapted to machine milking demonstrate the crucial role of suckling in stimulating OT release (Bar-Peled et al 1995;Krohn, 2001).…”
Section: Discussionmentioning
confidence: 88%